POSSIBILITY OF USE OF BIOINSECTICIDE AZADIRACHTIN AND SOME SYNTHETIC AND SEMI-SYNTHETIC INSECTICIDES IN HELICOVERPA ARMIGERA CONTROL ON SWEET PEPPER - Tamaš, Nenad; Sretenović, Marko; Miletić, Novica (Journal of Agricultural Sciences (Belgrade), 2024)
During 2019 and 2020, field experiments were performed on sweet pepper crops to determine the efficacy of chemical insecticides (lambda-cyhalothrin, flubendiamide), semi-synthetic (emamectin benzoate), and biological pesticide (azadirachtin) in the control of cotton bollworm (Helicoverpa armigera). The experiments were performed in randomized complete block design with four replications according to the standard EPPO method at the site of Veliko Gradište (Serbia). Flubendiamide was applied in 50 g/ha, lambda-cyhalothrin in 7.5 g/ha, emamectin benzoate in 375 g/ha, and azadirachtin in the amount of 0.75 g/ha. The intensity of the 2nd generation cotton bollworm infestation on sweet pepper at this locality was higher during 2020 compared to 2019. After performing two treatments for the 2nd generation, flubendiamide showed the highest efficacy, ranging from 92.42% (3DAT, 2020) to 95.56% (9DAT, 2019). Lambda-cyhalothrin had a satisfactory efficacy in the range of 81.93% (9DAT, 2020) to 90.63% (3DAT, 2019), and emamectin benzoate showed similar efficacy of 80.72% (9DAT, 2020) to 90.63% (3DAT, 2019). Azadirachtin as a biopesticide could gain a significant place in IPM programs for sweet pepper protection from H. armigera. However, it statistically showed a significantly lower efficacy than other insecticides (77.27%: 3DAT, 2020 to 86.67%: 9DAT, 2019).